First-line antibiotic prescription patterns for acute otitis media in children: A descriptive study using Japanese claims data (2014–2018). Issue 9 (September 2021) - Yamaguchi, Saori; Matsubayashi, Keisuke; Mizuno, Kayoko; Noda, Masahiro; Takeuchi, Masato; Kawakami, Koji
Abstract: Introduction: Acute otitis media is a highly prevalent disease in children. Although guidelines in many countries recommend amoxicillin as the first-line treatment for acute otitis media, the prescribing pattern in Japan is not clear. Our objective was to clarify the amoxicillin prescriptions as first-line antibiotics for acute otitis media and factors associated with amoxicillin prescriptions. Also, changes in amoxicillin prescriptions during the study period by medical facilities were investigated. Methods: Using an administrative claims database, we included new episodes of acute otitis media prescribed antibiotics in children under seven years of age between 2014 and 2018. The proportion of amoxicillin prescription was described. Using multivariate logistic regression analysis, factors associated with amoxicillin prescription were evaluated. Rate differences were calculated to describe changes in amoxicillin prescription by medical facilities. Results: 207, 213 episodes in 149, 929 patients were identified. Amoxicillin prescription was 24.0% and increased over the study period (P for trend <0.001). Characteristics of medical facilities were associated with amoxicillin prescriptions, and hospitals were more likely to prescribe amoxicillin (adjusted odds ratio: 1.71, 95% confidence intervals: 1.63 to 1.79). Compared to 2014, the range of increase in amoxicillin prescription in 2018 was greater in hospitals (14.9%) and pediatric clinics (10.5%) than in otolaryngology clinics (5.9%) and other specialty clinics (6.0%). Conclusions: During the study period, amoxicillin prescriptions had increased compared to 2014, but the proportion was still low. Clinics prescribed less amoxicillin than hospitals, and the range of increase was small. Our results suggested that some interventions focused on clinics are needed.